Bio-inspired preparation of Ag NPs, rGO, and Ag/rGO nanocomposites for acoustical, antioxidant, and plant growth regulatory studies - Prashant D. Sarvalkar; Anuj S. Jagtap; Neeraj R. Prasad; Amit R. Yaul; Kiran Kumar K. Sharma; Avinash A. Ramteke (Scientific Reports)
Abstract Acoustical properties are essential for understanding the molecular interactions in fluids, as they influence the physicochemical behavior of liquids and determine their suitability for diverse applications. This study investigated the acoustical parameters of silver nanoparticles (Ag NPs), reduced graphene oxide (rGO), and Ag/rGO nanocomposite nanofluids at varying concentrations. Ag NPs and Ag/rGO nanocomposites were synthesized via a Bos taurus indicus (BTI) metabolic waste-assisted method and characterized using advanced techniques, including XRD, TEM, Raman, DLS, zeta potential, and XPS. The synthesized nanocomposites were evaluated for their acoustical, antioxidant, and plant growth-regulatory properties. Acoustical analysis revealed a linear relationship between the nanofluid concentration and density, with key parameters such as adiabatic compressibility, apparent molar compressibility, and apparent molar volume increase at lower concentrations. Irregular changes in ultrasonic velocity and other parameters at 0.025 mol/dm3 suggest unique nanoparticle-solvent interactions. The Ag/rGO nanocomposites exhibited superior antioxidative potential compared to Ag NPs, with DPPH scavenging activity reaching 65.69% and ABTS scavenging activity reaching 65.01% at 100 µg/mL. Plant growth studies have demonstrated enhanced germination rates (100% in spinach and 40% in fenugreek) and improved root and shoot elongation at 0.0025–0.005 mol/dm3. This study bridges the gap in understanding the acoustical and multifunctional properties of nanocomposites for biomedical, agricultural, and environmental applications.